Image-Derived Input Function from Cardiac Gated Maximum a Posteriori Reconstructed PET Images in Mice - Locke, Landon W. (2011)
PURPOSE: To determine if accurate image-derived input functions (IDIF) can be measured from cardiac gated PET images reconstructed using ordered subset expectation maximization – maximum a posteriori (OSEM-MAP) without further correction. PROCEDURES: IDIFs from the left ventricle (LV) were measured from cardiac gated PET images reconstructed using OSEM-MAP with CT-based attenuation correction for 5 C57/BL6 mice. The accuracy of the IDIF was tested against blood samples using Bland-Altman analysis. RESULTS: Image-derived blood radioactivity concentration values were not significantly different from sampled blood values at two late time points as determined by a paired t-test (P=0.97). Bland-Altman analysis revealed a mean difference of −0.06 µCi/ml (1%). Using kinetics analysis, the mean myocardial FDG uptake rate constant based on the IDIF was comparable to values reported in the literature based on physical blood sampling. CONCLUSIONS: Accurate IDIFs can be obtained non-invasively. Although reconstruction times are increased, no further spillover corrections are necessary for IDIFs derived from gated, OSEM-MAP reconstructed images with attenuation correction.